Unfolding the rise of corporate communications: an Asian perspectives - Abdullah, Zulhamri; Ahmad, Zeti Azreen; Tugiman, Nursafwah (Universiti Putra Malaysia Press, 2024)
In today’s fast-paced and interconnected business world, effective communication has become a critical component of corporate success.Whether it is communicating with employees, shareholders, customers,or other stakeholders, the ability to convey information clearly and persuasively is essential for achieving business objectives. This book on corporate communication is designed to provide readers with a comprehensive understanding of the importance of communication in the corporate world, as well as the tools and techniques needed to effectively communicate in various contexts. The book covers a range of topics, from the fundamentals of corporate communication theories and models to the practical applications of communication in corporate settings. Throughout the book, readers will learn about the various forms of corporate communication, including internal and external communication,crisis communication, and public relations. They will also explore the role of technology in corporate communication, including social media, email, and other digital channels. One of the key themes of this book is the importance of authenticity and transparency in corporate communication. Today’s consumers and stakeholders demand honesty and openness from the companies they do business with, and effective communication is essential for building trust and maintaining a positive reputation. The book is designed to be accessible to both students and professionals, with clear explanations and practical examples that illustrate key concepts. Whether you are a business student, a corporate communications professional, or simply someone interested in learning more about the role of communication in the modern business world, this book is an invaluable resource. From communication to strategic reputation – here we present an international book aiming to advance knowledge and professional skills about strategic reputation and communication for a global communicator to improve the practice of reputation management in various industrial sectors such as airlines, petroleum, telecommunication, information communication technology, food and beverages, banking, and energy, as well as in dynamic government sectors such as public services, and ministries. Corporate communication has become a distinctive discipline of strategic management. Specifically, it is at the heart of strategic management. This discipline vigorously contributes to the organisation’s internal and external functions and its strategy development, especially in key areas such as stakeholder relations, reputation management, corporate governance, corporate social responsibility, and community relations. This book is written primarily to enrich the knowledge of corporate communication management for the following groups of readers: a. Postgraduate and undergraduate students studying in the fields of corporate communication, public relations, new media, and marketing (strongly recommended for Master of Corporate Communication and MBA students). b. Practitioners (managers, executives, and analysts) practising corporate communication, public relations, new media and marketing. c. Organisational leaders who run and lead an excellent organisation (including unit, centre, department, and suchlike) in the national and international contexts. d. Academics/researchers who are interested in the areas of corporate communication, public relations, business strategy, marketing communication, and media studies. It is important to say that this book presents key concepts of corporate communication including stakeholder relations; reputation management and corporate branding; corporate social responsibility and community relations; and corporate governance, which goes beyond traditional public relations (which is strongly associated with publicity and propaganda per se) as widely discussed in many PR books. Public relations here is more likely called ‘corporate communication’ as it will articulate new approaches as to how important its role is in improving an organisation’s strategy development and satisfying its strategic constituencies. This book gives readers awareness and understanding of the new era of strategic communication and how knowledge of corporate communication can feed practitioners’ minds about three pillars of competencies: grasping global managerial expertise, enhancing trust and credibility, and improving regulation especially by abiding by a universally exclusive code of ethics, Code of Athens. Although there are a number of books on corporate communication that have been published, many discuss typical communication skills which are mainly technical and vocational. The notion of corporate communication discussed in this book goes beyond media relations and business communication. In today’s competitive business environment, corporate communication can no longer afford to be housed in the area of mass communication or marketing per se. This emerging notion, which is interdisciplinary, is integrated with strategic management and business policy. At the managerial level of communication, a recent study found that organisational leaders expected that practitioners of corporate communication formulate the policy of corporate communication and strategic planning to improve their organisational reputation. Proudly, this book is intentionally written based on international (global) perspectives by taking into account issues and case studies in transitional (fast developing) countries, which challenged western traditional PR theories and practices. A transitional country here refers to an Asian country which has huge potential in an emerging global market. In addition, it is believed that Asian countries are more multiethnic, multi-lingual and multi-religious as compared to western and developed countries. Although many issues and practices in developed and developing countries are considered universal, every country has unique local culture that needs to be understood and promoted to the world. It needs international and cultural diversity management. Thus, it may also suit readers who are concerned with globalisation and ‘glocalisation’ (adaptation to local orientation). Additionally, recent models of corporate communication (reputation management, corporate marketing communication, and crisis management) are discussed thoroughly, coupled with presenting case studies in transitional countries.